PERANCANGAN SISTEM INFORMASI WISATA PADA DINAS PARIWISATA KOTA TANGERANG BERBASIS WEBSITE - Nurul Rahmah Tsania (2023)
Currently tourism is developing very rapidly, many new tours in various regions are one of the proofs. However, there are still obstacles in the development of tourism at this time, namely there are still many tours that are not widely known by the public. One of them is tourism in the city of Tangerang, where there are still many tours in the city of Tangerang that are not yet known by the public. Currently, Tangerang City Tourism does not even have a special platform regarding Tangerang City tourism which can be accessed at any time by all members of the public. The research objective is to design a website-based travel information system for Tangerang City. This study uses the SDLC (System Development Life Cycle) method with the waterfall model which gradually uses the PIECES method to analyze specific problems and the black box testing method for testing the system found on the website. The modeling system used is the Unified Modeling Language (UML) to form a system in the tourism information system for the Tangerang City Tourism Office. This research produces a website-based tourist information system that is expected to make it easier for visitors to buy tourist tickets, as well as assist the Tourism Office in recording visitors who come to tourist attractions.